Discovery of 5-(4-methylpiperazin-1-yl)-2-nitroaniline derivatives as a new class of SIRT6 inhibitors. Issue 16 (15th August 2020) - Sun, Weining; Chen, Xiuli; Huang, Shenzhen; Li, Wenpei; Tian, Chenyu; Yang, Shengyong; Li, Linli
Graphical abstract: Abstract: SIRT6 is a deacetylase of histone H3 and inhibitors of SIRT6 have been thought as potential agents for treatment of diabetes. Herein we report the discovery of a series of new SIRT6 inhibitors containing the skeleton 1-phenylpiperazine. Among them, compound 5-(4-methylpiperazin-1-yl)-2-nitroaniline (6d ) is the most potent one, which showed an IC50 value of 4.93 μM against SIRT6 in the Fluor de Lys (FDL) assay. It displayed KD values of 9.76 μM and 10 μM in surface plasmon resonance (SPR) and isothermal titration calorimetry (ITC) assays, respectively. In selectivity assay, 6d showed no activity against other members of the HDAC family (SIRT1-3 and HDAC1-11) at concentrations up to 200 µM. In a mouse model of type 2 diabetes, 6d could significantly increase the level of glucose transporter GLUT-1, thereby reducing blood glucose. Overall, this study provides a promising lead compound for subsequent drug discovery targeting SIRT6.